Field and laboratory assessments of the friction coefficient at a railhead. (January 2016) - Moreno-Ríos, Marisa; Gallardo-Hernández, Ezequiel A; Vite-Torres, Manuel; Peña-Bautista, Alejandro
The aim of this work was to prove that the oil applied to the wheel flange using on-board lubricators not only alters the friction coefficient between wheel and rail but also influences the braking and acceleration performance of trains on one of the lines of the metro in Mexico City. A series of tests were carried out in the presence of an oil lubricant, both in the laboratory and in the field, using a pendulum tester. It was observed that the oil migrated from the rail corner to the top of the rail. In another set of experiments, water was sprayed onto the lubricant on the top of the rail. The results indicated that under these conditions, the friction coefficient has a low value in rail sections where a high value of the friction coefficient is required. Tests with water/oil mixtures presented similar levels of friction to the oil-only tests. A set of tests were performed after the rail surface was cleaned and the oil lubricant and water were applied together. The laboratory and field tests showed similar behaviour trends for the friction coefficient. The pendulum method can be used to assess railhead friction on short-length sections of rail. Points are made regarding the conditioning of the pads and calibration of the pendulum arm.